White surface layer gypsum as well as preparation method and application thereof
By combining and processing the modified citric gypsum with other components, a white surface gypsum with high whiteness, high fineness and high bonding strength was prepared, which solved the color and construction problems of the existing surface gypsum and achieved the Efficient construction and cost reduction, with auxiliary insulation and breathing functions.
Patent Information
- Application Number
- CN202411610039.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing surface gypsum material is gray or yellow in color, and has low bonding strength, which is prone to hollowing, cracking and roughness, resulting in high construction and maintenance costs, and additional putty layer process is required to cover the background color. Impacts aesthetics and comfort.
Using a combination of modified citric acid gypsum, heavy calcium, cellulose, retarder and modified gray calcium, white surface gypsum is prepared through high-temperature calcination, irradiation treatment and rolling technology to improve its whiteness, fineness and viscosity The junction strength avoids yellowing, hollowing, and cracking, and eliminates the putty layer process.
A white surface gypsum with high whiteness, high fineness and high bonding strength was obtained, which solved the color and construction cost of traditional surface gypsum, ensured that the wall was smooth and not rough, reduced construction and maintenance costs, and was equipped with Assist insulating and breathing functions.
Smart Images

Figure BDA0005130703790000051 
Figure BDA0005130703790000061 
Figure BDA0005130703790000071
Abstract
Description
Technical Field
[0001] The present application belongs to the field of building materials and relates to a white surface gypsum and a preparation method and application thereof. Background Art
[0002] In the existing interior wall construction technology, most projects use lightweight interior wall plastering gypsum instead of traditional cement mortar to carry out interior wall dry area plastering projects to solve the problems of hollowing and cracking that often occur in cement mortar walls.
[0003] At present, the bottom layer of lightweight plastering gypsum uses calcined desulfurized gypsum (hemihydrate gypsum CaSO4·1 / 2H2O) as the main cementing material. It has high bonding strength, no hollowing, and no cracking, but the surface is rough and the material is mostly gray or yellow. In order to cover the color and solve the problem of surface roughness, the surface of the bottom layer of lightweight plastering gypsum needs to be covered. The general process flow is as follows:
[0004] Bottom layer lightweight plaster - surface layer plaster - interior wall putty - interior wall decoration layer.
[0005] As shown in the above process flow, the purpose of adding a surface plaster process to the wall surface of the bottom layer of lightweight plaster is to increase the flatness of the wall to meet the acceptance standard. However, since the raw materials of traditional surface plaster materials on the market are the same as the raw materials of the bottom layer of lightweight plaster, their colors are gray or yellow, so 2-3 coats of interior wall putty construction must be carried out to cover the base color of the plaster layer before the interior wall decoration layer construction can be carried out; if the interior wall putty construction process is omitted, the interior wall decoration layer cannot cover the base color of the plaster layer, affecting the aesthetics and comfort. However, ordinary interior wall putty materials have the hidden dangers of low strength and easy hollowing and cracking.
[0006] Therefore, a white surface gypsum is currently needed to replace the traditional surface plaster gypsum layer, ensuring that its color is pure white, high whiteness, high fineness, high bonding strength, and will not produce hollow cracks and rough wall surface; it can save the putty layer process, shorten the construction time, and reduce the construction cost and secondary maintenance cost. The process flow is as follows:
[0007] Base layer of lightweight plaster – white top layer of plaster – interior wall decoration layer. Summary of the invention
[0008] In order to solve the above problems, the present application provides a white surface gypsum and its preparation method and application. The white surface gypsum obtained in the present application has high whiteness, high fineness and high strength, and will not turn yellow after being applied to the wall, and will not cause problems such as cracking, hollowing and sanding of the surface layer, and can also ensure that the wall surface is smooth and not rough. The specific technical solutions of the present application are as follows:
[0009] The present application provides a white surface gypsum, comprising the following components in parts by weight:
[0010] 500-570 parts of modified citric acid gypsum, 400-460 parts of heavy calcium, 2-4 parts of cellulose, 1-3 parts of retarder, 20-30 parts of lime;
[0011] The modified citric acid gypsum is prepared by the following method: calcining citric acid gypsum powder at high temperature, adding a surfactant and mixing, and irradiating the mixture; the surfactant comprises at least one of sodium alginate and sodium rosin acid;
[0012] The limestone includes any one of modified limestone and ordinary limestone. The ordinary limestone is commercially available; the modified limestone is obtained by compounding modified calcium hydroxide, calcium oxide, and calcium carbonate in a mass ratio of (8-9):2:(0.2-0.5);
[0013] The modified calcium hydroxide is prepared by the following method:
[0014] Quicklime with a particle size of 1-3 mm and isopropanol monomer are mixed in a mass ratio of 0.5-2:1, and 3-10 times the volume of the mixture of water above 60°C are added. After stirring, the temperature is gradually increased, and after a period of reaction, the temperature is lowered to below 58°C, and decompression dehydration is started. The obtained product is vacuum dried below 58°C to obtain modified calcium hydroxide.
[0015] Optionally, the surfactant is obtained by compounding sodium alginate and sodium rosinate in a mass ratio of (1-2):(1-3); preferably, it is 2:1.
[0016] Optionally, the surfactant is added in an amount of 0.2-0.5% by weight of the citric acid gypsum powder.
[0017] Optionally, the irradiation conditions are: irradiation with β-rays at a dose of 100-150 kGy for 10-30 minutes.
[0018] Optionally, the high temperature calcination condition is: calcination at 200-250° C. for 5-10 minutes.
[0019] Optionally, the fineness of the citric acid gypsum powder is 10-50 mesh.
[0020] Optionally, the heavy calcium includes two particle sizes, and in terms of mass percentage, the particle size of 0.5-1.5 um accounts for 50-70%; the particle size of 2.0-3.0 um accounts for 30-50%.
[0021] Optionally, the cellulose includes at least one of cellulose acetate and hydroxyethyl cellulose; preferably, cellulose acetate and hydroxyethyl cellulose are compounded in a mass ratio of 1:1-3.
[0022] Optionally, the retarder includes sucrose, sodium glucose phosphate, sodium metaphosphate, sodium carboxymethyl cellulose, and sodium carboxymethyl cellulose; preferably, the retarder is obtained by compounding sucrose, sodium glucose phosphate, and sodium metaphosphate in a mass ratio of (1-2):(1-3):1.
[0023] The present application also provides a method for preparing the above gypsum, comprising the following steps:
[0024] According to the formula, the modified citric acid gypsum and lime lime are first mixed and rolled for 2-4 minutes, and then stirred continuously until the mixture is fully mixed. Then, heavy calcium, cellulose, and retarder are added in sequence while stirring, and the mixture is rolled again for 5-10 minutes and stirred to obtain a white surface gypsum.
[0025] The rolling pressure is set to 50-100Mpa.
[0026] Furthermore, the present application also provides the use of the above-mentioned white surface gypsum in the preparation of high-strength and high-whiteness building decoration materials.
[0027] The beneficial effects of this application include but are not limited to:
[0028] 1. The white surface gypsum prepared in this application will not turn yellow, crack or hollow after being applied to indoor walls.
[0029] After high-temperature calcination, most of the citric acid molecules remaining in the citric acid gypsum are decomposed, and the whiteness of the citric acid gypsum is improved; secondly, surfactants (sodium alginate and sodium rosin acid) are added and combined with irradiation treatment, and the sodium alginate and sodium rosin acid under irradiation have a good synergistic effect; on the one hand, the pore structure of the citric acid gypsum is improved, its porosity is reduced, the pore defects are improved, and the strength of the citric acid gypsum is improved; on the other hand, the particle size of the citric acid gypsum is reduced, and the apparent density of the citric acid gypsum is reduced, so that the reaction between the citric acid gypsum and the lime calcium is weaker, the amount of calcium citrate produced is small, and the particle size of the generated calcium citrate is larger, it has certain gelling properties, and the mixing effect with other components is better, so that the citric acid gypsum can still have good strength after being mixed with the lime calcium.
[0030] Among them, sodium alginate contains a large number of hydroxyl and carboxyl groups in its molecular structure. In the later stage of preparing mortar with gypsum, it forms hydrogen bonds with water molecules and exhibits excellent water retention, ensuring that the wall surface does not crack. In addition, sodium alginate has an ookie-triangular structure and is extremely stable, which ensures the water retention of gypsum during long-term use without cracking.
[0031] 2. Furthermore, the present application further improves the strength and water retention of the white surface gypsum by optimizing the ratio between specific components; the white surface gypsum prepared in the present application has excellent performance, with water retention reaching 97%, whiteness reaching 98%, flexural strength, compressive strength, and tensile bond strength reaching 8.0MPa, 9.5MPa, and 2.3MPa, respectively; it overcomes the current technical barriers that gypsum whiteness, strength, and water retention are difficult to achieve simultaneously.
[0032] In addition, the addition of lime lime obtained by a specific method into the formula further improves the flexural strength, compressive strength, and tensile bond strength of the white surface gypsum.
[0033] 3. The white surface gypsum of this application overcomes the problems of the base color of the traditional surface gypsum and the rough wall surface after application. It has high whiteness, high fineness, non-rough wall surface, high bonding strength (not inferior to the whiteness, fineness, and bonding strength of putty materials), and will not produce hollowing and cracking. It can replace the traditional surface plastering gypsum layer, and also saves the putty layer process in the traditional process, shortens the construction time, and reduces the construction cost and secondary maintenance cost. The specific process flow is: bottom layer lightweight plastering gypsum - white surface gypsum - interior wall decoration layer, and has auxiliary thermal insulation performance and breathing function.
[0034] 4. The initial setting time of the white surface gypsum of the present application is about 1.7 hours and the final setting time is about 2 hours during the construction process. The setting time is appropriate and will not cause construction inconvenience due to too early setting, which greatly improves the work efficiency. DETAILED DESCRIPTION
[0035] The present application is described in detail below in conjunction with the examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials in the examples of the present application are purchased through commercial channels. In addition, the weight parts of the components in the following embodiments can be replaced by weight units such as "gram", "kilogram" and "jin" in equal proportion.
[0036] The lime used in Examples 1-8 is common lime (commonly available on the market), and the lime used in Examples 9-10 is modified lime.
[0037] Embodiment 1 A white surface gypsum is composed of the following components in parts by weight:
[0038] 550 parts of modified citric acid gypsum, 430 parts of heavy calcium, 3 parts of cellulose, 2 parts of retarder, and 25 parts of lime calcium.
[0039] The retarder is obtained by compounding sucrose, sodium glucose phosphate and sodium metaphosphate in a mass ratio of 1:1:1;
[0040] The cellulose is obtained by compounding cellulose acetate and hydroxyethyl cellulose in a mass ratio of 1:1;
[0041] The heavy calcium includes two particle sizes, and by mass percentage, the particle size of 0.5-1.5um accounts for 70%; the particle size of 2.0-3.0um accounts for 30%.
[0042] Modified citric acid gypsum is prepared by the following method:
[0043] The citric acid gypsum was crushed to 10 meshes to obtain citric acid gypsum powder, which was irradiated with β-rays at a dose of 100 kGy for 10 minutes, and a surfactant accounting for 0.2% by weight of the citric acid gypsum powder was added, followed by calcination at 200° C. for 5 minutes.
[0044] The configuration of the surfactant in the modified citric acid gypsum is shown in Table 1 below.
[0045] A method for preparing white surface gypsum comprises: firstly mixing modified citric acid gypsum and lime lime according to a formula, rolling for 2 minutes, continuously stirring until the mixture is fully mixed, then adding heavy calcium, cellulose and a retarder in sequence while stirring, rolling again for 5 minutes and stirring to obtain white surface gypsum;
[0046] The rolling pressure is set to 80Mpa.
[0047] The white surface gypsum obtained in this embodiment was tested for performance, and the test results were as follows:
[0048] 1) Flexural strength and compressive strength: compressive strength test shall be carried out in accordance with GB / T28627-2023 "Plastering Gypsum".
[0049] 2) Tensile bonding strength: The tensile bonding strength test shall be carried out in accordance with GB / T28627-2023 "Plastering Gypsum".
[0050] 3) Water retention rate: Test the water retention rate in accordance with GB / T28627-2023 "Plaster Gypsum".
[0051] 4) The test was performed using a digital whiteness meter SBDY-1. The specific test results are shown in Table 1.
[0052] Table 1 Effect of citric acid gypsum obtained with different surfactants on white surface gypsum
[0053]
[0054]
[0055] According to the results in the above table, after adding the surfactant obtained by compounding sodium alginate: sodium rosin acid in the ratio of (1-2): (1-3), the white surface gypsum obtained has high whiteness and significantly improves the flexural strength, compressive strength, tensile bond strength and water retention rate.
[0056] After high-temperature calcination, most of the citric acid molecules remaining in the citric acid gypsum are decomposed, and the whiteness of the citric acid gypsum is improved; secondly, surfactants (sodium alginate and sodium rosin acid) are added and combined with irradiation treatment, and the sodium alginate and sodium rosin acid under irradiation have a good synergistic effect; on the one hand, the pore structure of the citric acid gypsum is improved, its porosity is reduced, the pore defects are improved, and the strength of the citric acid gypsum is improved; on the other hand, the particle size of the citric acid gypsum is reduced, and the apparent density of the citric acid gypsum is reduced, so that the reaction between the citric acid gypsum and the lime calcium is weaker, the amount of calcium citrate produced is small, and the particle size of the generated calcium citrate is larger, it has certain gelling properties, and the mixing effect with other components is better, so that the citric acid gypsum can still have good strength after being mixed with the lime calcium.
[0057] In addition, the molecular structure of sodium alginate contains a large number of hydroxyl and carboxyl groups. In the later stage of gypsum preparation of mortar, it forms hydrogen bonds with water molecules and exhibits excellent water retention, ensuring that the wall surface does not crack. In addition, the structural stability of sodium alginate is extremely strong, ensuring the water retention of gypsum during long-term use without cracking.
[0058] In addition, during the component addition process, it was found that the components would be mixed faster and more evenly if the modified citric acid gypsum and lime lime were fully mixed first, and then the heavy calcium, cellulose, and retarder were added and stirred.
[0059] Example 2 A white surface plaster
[0060] According to the screening results of Example 1, the surfactant is selected to be obtained by compounding sodium alginate and sodium rosin acid in a mass ratio of 2:1, and the irradiation conditions are screened. The remaining steps are the same as in Example 1.
[0061] Table 2 Effect of citric acid gypsum obtained under different irradiation conditions on white surface gypsum
[0062]
[0063] According to the data in the table above, irradiation at 100-150 kGy for 10-30 minutes has the best effect, which can further enhance the flexural strength and compressive strength.
[0064] The irradiation amount within this range can reduce the weight average molecular weight of sodium alginate to below 12,000, so that it can better adsorb sodium rosin acid and have a better synergistic effect with it.
[0065] Example 3 A white surface plaster
[0066] According to the screening results of Example 1 and Example 2, the surfactant is selected to be a mixture of sodium alginate and sodium rosin acid in a mass ratio of 2:1, and the irradiation condition is 120 kGy for 10 minutes. The high temperature calcination conditions are screened. The remaining steps are the same as Example 1.
[0067] Table 3 Effect of citric acid gypsum obtained under different high temperature calcination conditions on white surface gypsum
[0068]
[0069]
[0070] According to the table above, the calcination effect at 200-250℃ is relatively the best. At this temperature, the gypsum structure will not be damaged and the strength is the best. At the same time, it can further effectively remove the residual citric acid and improve the whiteness of the gypsum.
[0071] Example 4
[0072] According to the screening results of Example 1, Example 2, and Example 3, the surfactant is selected to be a mixture of sodium alginate and sodium rosin acid in a mass ratio of 2:1, and the irradiation condition is 120 kGy for 10 minutes. The high temperature calcination condition is calcination at 200° C. for 5 minutes. The selection of cellulose is screened, and the remaining steps are the same as in Example 1.
[0073] Table 4 Effect of citric acid gypsum obtained by adding different cellulose on white surface gypsum
[0074]
[0075]
[0076] According to the data in the above table, the white surface gypsum prepared by adding cellulose obtained by compounding cellulose acetate: hydroxyethyl cellulose not only has higher flexural strength, compressive strength, and tensile bonding strength, but also can further improve the whiteness and water retention of the white surface gypsum paste.
[0077] Example 5
[0078] This embodiment is carried out based on the experimental results of the above embodiments 1-4.
[0079] A white surface gypsum, composed of the following components in parts by weight:
[0080] 550 parts of modified citric acid gypsum, 430 parts of heavy calcium, 3 parts of cellulose, 2 parts of retarder, and 25 parts of lime calcium. The retarder is obtained by compounding sucrose, sodium glucose phosphate, and sodium metaphosphate in a mass ratio of 1:1:1;
[0081] The cellulose is obtained by compounding cellulose acetate and hydroxyethyl cellulose in a mass ratio of 1:1;
[0082] The heavy calcium includes two particle sizes, and by mass percentage, the particle size of 0.5-1.5um accounts for 70%; the particle size of 2.0-3.0um accounts for 30%.
[0083] Modified citric acid gypsum is prepared by the following method:
[0084] The citric acid gypsum was crushed to 10 meshes to obtain citric acid gypsum powder, which was irradiated with β-rays at a dose of 120 kGy for 10 minutes, and a surfactant accounting for 0.2% of the weight of the citric acid gypsum was added, followed by calcination at 200° C. for 5 minutes.
[0085] The surfactant is prepared by mixing sodium alginate and sodium rosinate in a mass ratio of 2:1.
[0086] A method for preparing white surface gypsum comprises: firstly mixing modified citric acid gypsum and lime lime according to a formula, rolling for 2 minutes, continuously stirring until the mixture is fully mixed, then adding heavy calcium, cellulose and a retarder in sequence while stirring, rolling again for 5 minutes and stirring to obtain white surface gypsum;
[0087] The rolling pressure is set to 80Mpa.
[0088] Example 6 A white surface gypsum, which differs from Example 5 in that the component ratio is different, and specifically consists of the following components in parts by weight:
[0089] 570 parts of modified citric acid gypsum, 400 parts of heavy calcium, 2 parts of cellulose, 1 part of retarder, and 20 parts of lime. The rest is the same as in Example 4.
[0090] The preparation method of the modified citric acid gypsum and the preparation method of the white surface layer gypsum are also the same as those in Example 4.
[0091] Example 7 A white surface gypsum, which differs from Example 5 in that the component ratio is different, and specifically consists of the following components in parts by weight:
[0092] 600 parts of modified citric acid gypsum, 400 parts of heavy calcium, 2.3 parts of cellulose, 1 part of retarder, and 20 parts of lime. The rest is the same as in Example 4.
[0093] The preparation method of the modified citric acid gypsum and the preparation method of the white surface layer gypsum are also the same as those in Example 4.
[0094] Example 8 A white surface gypsum, which differs from Example 5 in that the component ratio is different, and specifically consists of the following components in parts by weight:
[0095] 600 parts of modified citric acid gypsum, 500 parts of heavy calcium, 3 parts of cellulose, 4 parts of retarder, and 40 parts of lime. The rest is the same as in Example 4.
[0096] The preparation method of the modified citric acid gypsum and the preparation method of the white surface gypsum are also the same as those in Example 4.
[0097] Example 9 is a white surface gypsum, which is different from Example 5 in that the lime lime used is modified lime lime. The modified lime lime is obtained by compounding modified calcium hydroxide, calcium oxide and calcium carbonate in a mass ratio of 8.5:2:0.2;
[0098] The modified calcium hydroxide is prepared by the following method:
[0099] Quicklime with a particle size of 1-3 mm and isopropanol monomer are mixed in a mass ratio of 0.5:1, and 62°C water is added in an amount 10 times the volume of the mixture. The temperature is raised while stirring. After a certain period of reaction, the temperature is lowered to about 57°C, and dehydration is performed under reduced pressure. The product is vacuum dried at about 57°C to obtain modified calcium hydroxide.
[0100] The remaining components of the white surface layer gypsum are the same as those in Example 4.
[0101] The preparation method of the modified citric acid gypsum and the preparation method of the white surface gypsum are also the same as those in Example 4.
[0102] Example 10 differs from Example 9 in that propylene glycol is used to replace isopropyl alcohol, and the rest is the same as Example 9.
[0103] Comparative Example 1 is different from Example 5 in that no surfactant is added to the modified citric acid gypsum.
[0104] Comparative Example 2 is different from Example 5 in that the modified citric acid gypsum is not irradiated.
[0105] The difference between Comparative Example 3 and Example 5 is that the gypsum used is different, namely, ordinary desulfurized gypsum.
[0106] Comparative Example 4 is different from Example 5 in that the citric acid gypsum is not subjected to any treatment.
[0107] Comparative Example 5 is different from Example 5 in that citric acid gypsum is replaced by raw gypsum CaSO4·2H2O (white, a kind of natural gypsum).
[0108] Test Example 1
[0109] 1) The white surface gypsum prepared in the above Examples 5-8 and Comparative Examples 1-5 was subjected to quality inspection. The specific inspection results are shown in Table 5 below.
[0110] 2) Detect cracking:
[0111] The white surface plaster prepared in the above Examples 5-8 and Comparative Examples 1-5 was applied to the wall surface with a thickness of 1.0 cm ± 0.1 cm. After the wall surface was completely dry, water was sprayed on the target wall surface until the surface was moistened, and then hot air at 20° C. was continuously blown. The state of the target wall surface was observed after 3 months and 6 months, as shown in Table 6 below.
[0112] Table 5 Quality inspection
[0113]
[0114]
[0115] According to the above table, the white surface gypsum obtained in Examples 5-6 has relatively the best performance in terms of gypsum whiteness, flexural strength, compressive strength, tensile bond strength, and water retention rate, among which Example 4 performs best.
[0116] The comparison of the effects of Examples 5-6 and 6-7 shows that the ratio of modified citric acid gypsum to other components: heavy calcium, cellulose, retarder, lime calcium has a great influence on the white surface gypsum. In practice, it is found that when the weight ratio of each component is 500-570 parts of modified citric acid gypsum, 400-460 parts of heavy calcium, 2-4 parts of cellulose, 1-3 parts of retarder, and 20-30 parts of lime calcium, the beneficial effect of the obtained white surface gypsum is the best.
[0117] The comparison of the effects of Examples 5-6 and Comparative Examples 3-4 shows that the surface gypsum prepared by the modified citric acid gypsum added in the present application has better whiteness, strength and water retention performance than the surface gypsum prepared by desulfurized gypsum and ordinary citric acid gypsum on the market.
[0118] Comparison of the effects of Examples 5-6 and Comparative Examples 1-2 shows that high-temperature calcination of citric acid gypsum combined with surfactant and irradiation treatment can further remove citric acid and improve the whiteness, flexural strength, compressive strength, tensile bond strength, and water retention of gypsum.
[0119] The reason is that the irradiated sodium alginate and sodium rosin acid have a good synergistic effect and can reduce the particle size and surface area of citric acid gypsum. The citric acid gypsum at this particle size reacts weakly with lime calcium, and the amount of calcium citrate produced is small. The particle size of the generated calcium citrate is large, and it has certain gelling properties, and the mixing effect with other components is better, so that the citric acid gypsum can still have good strength after being mixed with lime calcium.
[0120] Irradiation treatment also changes the specific gravity of flaky particles, needle-shaped particles and columnar particles in building plaster to a certain extent. Combined with the structural characteristics of sodium alginate, it ensures that moisture exists in the gypsum mixing layer for a longer period of time, thereby improving the water retention rate after applying to the wall.
[0121] In addition, during the experiment, it was found that when the heavy calcium includes two particle sizes, by mass percentage, the particle size of 0.5-1.5um accounts for 50-70%; the particle size of 2.0-3.0um accounts for 30-50%, it can better fill the contact gap with other components and better enhance the strength of gypsum.
[0122] The effects of Example 5 and Example 9 are both excellent. Compared with the ordinary lime, the addition of modified lime can slightly improve the flexural strength, compressive strength and tensile bond strength of white gypsum; although the improvement is not very high, it is very difficult to further improve the strength on the basis of Example 5 while ensuring the whiteness.
[0123] When quicklime is in contact with water to generate calcium hydroxide, it forms a strong hydrogen bond with the hydroxyl group (-OH) in the isopropanol structure, becoming an anchoring functional group and forming an anchoring point on the surface of the calcium hydroxide particles, which can reduce the agglomeration of calcium hydroxide, improve its compatibility in the mixed material, and give full play to the characteristics of the lime itself, which may be the reason for the improvement of bonding strength. In addition, it was found during the experiment that when quicklime and isopropanol monomers were mixed at a mass ratio of 0.5-2:1 and 3-10 times the volume of water of the mixture was added, the modified lime added to the white surface gypsum had the best strength performance.
[0124] The modified lime in Example 9 has a better strength effect in the white surface gypsum than the modified lime in Example 10. It may be that isopropyl alcohol can better form a certain coating on the surface of calcium hydroxide during the reaction process, so that the lime and other components play a good synergistic role to improve the overall strength.
[0125] Table 6 below shows the wall quality test results at different cycles after painting:
[0126] Table 6 Quality inspection at different times
[0127]
[0128] According to the data in the table above, the white surface gypsum prepared in the embodiment of the present application is white after being applied to the wall for half a year, and no quality defects such as yellowing, hollowing, and cracking are found, and the wall surface is smooth. However, the comparative example 1 without adding surfactant, the comparative example 2 without irradiation treatment, and the comparative example 4 without any treatment of ordinary desulfurized gypsum and citric acid gypsum all show yellowing signs to varying degrees, and also show cracking phenomena to varying degrees, indicating that the white surface gypsum prepared in the present application has excellent performance, overcomes the problems of low whiteness of traditional surface gypsum, rough wall surface after application, and hollowing and cracking caused by putty layer, and overcomes the technical barriers that the whiteness, strength, and water retention rate of the wall surface of the traditional process are difficult to improve at the same time.
[0129] Moreover, the initial setting time after application is about 1.7 hours, and the final setting time is about 2 hours. The setting time is appropriate and will not cause construction inconvenience due to too early setting. This can greatly facilitate construction and improve work efficiency.
[0130] In summary, the white surface gypsum of the present application has high whiteness, high fineness, smooth wall surface, high bonding strength, and will not produce hollowing and cracking. It overcomes the problem of rough wall surface caused by the base color difference and low fineness of the traditional surface plastering gypsum layer, while also eliminating the putty layer process in the traditional process, shortening the construction time, and reducing the construction cost and secondary maintenance cost. The specific process flow is: bottom layer lightweight plastering gypsum - white surface gypsum - interior wall decoration layer, and has auxiliary thermal insulation performance and breathing function.
[0131] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A white surface gypsum, characterized in that: It includes the following components by weight: Modified citric acid gypsum 500-570 parts, heavy calcium 400-460 parts, cellulose 2-4 parts, retarder 1-3 parts, lime calcium 20-30 parts; The modified citric acid gypsum is prepared by the following method: citric acid gypsum powder is calcined at high temperature, a surfactant is added and mixed, and then irradiated to obtain the citric acid gypsum; the surfactant includes at least one of sodium alginate and sodium rosin acid; the lime includes any one of modified lime and ordinary lime.
2. The white surface plaster according to claim 1, characterized in that: The surfactant is obtained by compounding sodium alginate and sodium rosinate in a mass ratio of (1-2): (1-3); The surfactant is added in an amount of 0.2-0.5% of the weight of the citric acid gypsum powder.
3. The white surface gypsum according to claim 1, characterized in that: The irradiation conditions are: irradiation with β-rays at a dose of 100 to 150 kGy for 10 to 30 minutes.
4. The white surface gypsum according to claim 1, characterized in that: The high temperature calcination conditions are: calcination at 200-250°C for 5-10 minutes.
5. The white surface gypsum according to claim 1, characterized in that: The cellulose includes at least one of cellulose acetate and hydroxyethyl cellulose; preferably, the cellulose is obtained by compounding cellulose acetate and hydroxyethyl cellulose in a mass ratio of 1:(1-3).
6. The white surface gypsum according to claim 1, characterized in that: The modified lime is obtained by compounding modified calcium hydroxide, calcium oxide and calcium carbonate in a mass ratio of (8-9):2:(0.2-0.5); The modified calcium hydroxide is prepared by the following method: Quicklime with a particle size of 1-3 mm and isopropanol monomer are mixed in a mass ratio of 0.5-2:1, and 3-10 times the volume of the mixture of water above 60°C are added. After stirring, the temperature is gradually increased, and after a period of reaction, the temperature is lowered to below 58°C, and decompression dehydration is started. The obtained product is vacuum dried below 58°C to obtain modified calcium hydroxide.
7. The white surface gypsum according to claim 1, characterized in that: The heavy calcium includes two particle sizes, and by mass percentage, the particle size of 0.5-1.5um accounts for 50-70%; the particle size of 2.0-3.0um accounts for 30-50%; the fineness of the citric acid gypsum powder is 10-50 meshes.
8. The white surface plaster according to claim 1, characterized in that: The retarder includes at least one of sucrose, sodium glucose phosphate, sodium metaphosphate, sodium carboxymethyl cellulose, and sodium carboxymethyl cellulose; preferably, the retarder is obtained by compounding sucrose, sodium glucose phosphate, and sodium metaphosphate in a mass ratio of (1-2):(1-3):
1.
9. A method for preparing white surface gypsum as claimed in any one of claims 1 to 8, characterized in that: The steps include: According to the formula, the modified citric acid gypsum and lime lime are first mixed and rolled for 2-4 minutes, and then stirred continuously until the mixture is fully mixed. Then, heavy calcium, cellulose, and retarder are added in sequence while stirring, and the mixture is rolled again for 5-10 minutes and stirred to obtain a white surface gypsum. The rolling pressure is set to 50-100Mpa.
10. Use of the white surface gypsum as described in any one of claims 1 to 8 in preparing high-strength and high-whiteness building decoration materials.
Citation Information
Patent Citations
Lightweight plastering citric acid gypsum mortar
CN112897976A